Определение характеристик двухбарьерных фотодиодных структур с металлополупроводниковыми переходами - Yodgorova, D. M.; Karimov, A. V. (PE "Politekhperiodika", Book and Journal Publishers, 2005)
Based on experimental data of the current–voltage characteristics and the dependence of resistance on voltage in double-barrier m‑pGaAs–nGdS and modified m‑pGaAs–pGaAs–nGdS structures, calculations were carried out for the redistribution of voltage between forward- and reverse-biased junctions. The obtained data can be used to estimate the frequency range, the dependence of photosensitivity on the field, and to identify the mechanisms of photosensitivity in double-barrier structures with metal–semiconductor junctions.